IMMATURE TERATOMA OF THE SEMINAL VESICLE WITH SEMINOMA COMPONENTS IN AN ADULT MALE: A RARE CASE REPORT (Vietnam Journal of Community Medicine, 2026)
Teratomas are germ cell tumors containing derivatives of all three germ layers. Primary malignant teratoma of the seminal vesicle is an extremely rare extragonadal tumor, especially in young adult males. Accurate diagnosis and grading are crucial for determining the appropriate multimodal treatment strategy and prognosis. We report a case of a 31-year-old male presenting with a 2-month history of pelvic pain, dysuria, and difficulty in both urination and defecation. Laboratory investigations revealed significantly elevated tumor markers: AFP 1440 ng/mL. Abdominal CT scan identified a large, inhomogeneous, hypodense mass measuring 83 × 72 mm in the right pelvic region, corresponding to the right seminal vesicle location, which displaced the bladder and rectum. The patient underwent complete surgical resection. Grossly, the encapsulated mass measured 8 × 8 × 4 cm with a hard consistency and internal cystic spaces containing turbid fluid. Histopathological examination confirmed a diagnosis of immature teratoma with seminoma components. Due to a postoperative AFP rise (> 1600 ng/mL), the patient received BEP chemotherapy. After 2 cycles, clinical symptoms resolved, and AFP levels significantly decreased to 159 ng/mL. This case underscores the diagnostic challenge posed by sampling errors in needle biopsies of heterogeneous pelvic teratomas. The integration of high-level tumor markers with radical surgery and subsequent chemotherapy is essential for managing such rare malignant extragonadal germ cell tumors.
Keywords: Immature teratoma, seminal vesicle, seminoma.